Neutrophils: the forgotten cell in JIA disease pathogenesis - Petty Howard R; Jiang Kaiyu; Jarvis James N; Centola Michael (BMC, 2007)
Abstract Juvenile idiopathic arthritis (JIA) has long been assumed to be an autoimmune disease, triggered by aberrant recognition of "self" antigens by T-cells. However, systems biology approaches to this family of diseases have suggested complex interactions between innate and adaptive immunity that underlie JIA. In particular, new data suggest an important role for neutrophils in JIA pathogenesis. In this short review, we will discuss the new data that support a role for neutrophils in JIA, discuss regulatory functions that link neutrophils to adaptive immune responses, and discuss future areas of investigation. Above all else, we invite the reader to re-consider the use of the term "autoimmunity" as applied to the family of illnesses we collectively call JIA.